A Case Series: Effect of Comorbidities on the Outcomes of Prolotherapy Injection for Frozen Shoulder Patients - Sam N; Yusuf I; Idris I; Adnan E; Haryadi RD; Hamid F; Usman MA; Johan MP; Zainuddin AA (International Medical Case Reports Journal, 2023)
Nuralam Sam,1 Irawan Yusuf,1 Irfan Idris,2 Endy Adnan,3 Ratna Darjanti Haryadi,4 Firdaus Hamid,5 Muhammad Andry Usman,6 Muhammad Phetrus Johan,6 Andi Alfian Zainuddin7 1Department of Physical Medicine and Rehabilitation, Faculty of Medicine, Hasanuddin University, Makassar, Indonesia; 2Department of Physiology, Faculty of Medicine, Hasanuddin University, Makassar, Indonesia; 3Rheumatology Division, Department of Internal Medicine, Faculty of Medicine, Hasanuddin University, Makassar, Indonesia; 4Department of Physical Medicine and Rehabilitation, Faculty of Medicine, Airlangga University, Surabaya, Indonesia; 5Department of Microbiology, Faculty of Medicine, Hasanuddin University, Makassar, Indonesia; 6Department of Orthopedic, Faculty of Medicine, Hasanuddin University, Makassar, Indonesia; 7Department of Public Health, Faculty of Medicine, Hasanuddin University, Makassar, IndonesiaCorrespondence: Nuralam Sam, Department of Physical Medicine and Rehabilitation, Faculty of Medicine, Hasanuddin University, Perintis Kemerdekaan Street KM.11, Makassar, South Sulawesi, 90245, Indonesia, Email nuralamsam@unhas.ac.idAbstract: Frozen shoulder (FS) is a disease caused by an inflammatory condition that causes severe pain and decreased range of motion by loss of glenohumeral mobility. Frozen Shoulder restricts daily life’s functional aspect, increasing morbidity. Hypertension and diabetes mellitus are risk factors that make an FS poor prognosis during treatment because of the diabetes glycation process and hypertension-enhanced vascularization. Prolotherapy injects an irritant solution into the tendon, joints, ligaments, and joint spaces to release growth factors and collagen deposition, reducing pain, restoring joint stability, and increasing the quality of life. We report 3 cases of patients with confirmed FS. Patient A with no comorbidity, patient B with diabetes mellitus, and patient C with hypertension, with all patient’s chief complaints of shoulder pain and limited ROM, and symptoms affected the general quality of daily life. This patient was provided injection with Prolotherapy treatment combined with physical therapy intervention. Patient A had significantly improved ROM to maximum after 6 weeks with relieved pain and improved shoulder function. Patients B and C showed increased ROM, still tiny, decreased pain, and improved shoulder function. In conclusion, prolotherapy demonstrated a beneficial effect in a patient with FS with comorbidities, although not to the maximum extent in patients without comorbidity.Keywords: protherapy, frozen shoulder, comorbidity, range of motion, quality of life